1990
DOI: 10.1002/jmv.1890300315
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of diarrheal diseases in Venezuelan children to evaluate the efficacy of rhesus rotavirus vaccine

Abstract: The efficacy of a rhesus rotavirus vaccine (MMU 18006, serotype 3) against infantile diarrhea was evaluated by active home surveillance of a group of 320 children 1-10 months of age in Caracas, Venezuela. During a 1 year period following oral administration of vaccine or placebo under a double-masked code, over 600 diarrheal episodes were detected. Etiologic studies revealed that heat-stable toxin (ST) producing enterotoxigenic E. coli (ETEC) was the most common diarrheal agent detected (34%) followed by enter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 33 publications
0
42
1
1
Order By: Relevance
“…The failure of monovalent live RV vaccines to induce significant protection in children has been attributed to their lack of induction of heterotypic protective antibody responses to multiple RV serotypes. Consequently, a successful RV vaccine may need to induce broadly reactive or neutralizing antibodies to the major serotypes of RV (serotypes G1 to G4) commonly seen in children (29). Natural HRV infections in children induce increased rates of protection from reinfection and diarrhea following each subsequent RV infection, and secondary infections are most often caused by a different G serotype (34).…”
Section: Discussionmentioning
confidence: 99%
“…The failure of monovalent live RV vaccines to induce significant protection in children has been attributed to their lack of induction of heterotypic protective antibody responses to multiple RV serotypes. Consequently, a successful RV vaccine may need to induce broadly reactive or neutralizing antibodies to the major serotypes of RV (serotypes G1 to G4) commonly seen in children (29). Natural HRV infections in children induce increased rates of protection from reinfection and diarrhea following each subsequent RV infection, and secondary infections are most often caused by a different G serotype (34).…”
Section: Discussionmentioning
confidence: 99%
“…In industrialized countries, clinical trials for three Jennerian vaccines using attenuated animal strains demonstrated good efficacy against severe rotavirus disease [20,69,79,91,[95][96][97][98]. In contrast, these vaccines failed to provide protection in challenging impoverished settings where the vaccine would be most critical to saving lives [32,40,41,48,49,85].…”
Section: Development Of Rotavirus Vaccinesmentioning
confidence: 99%
“…The RRV-MMU strain underwent 9 passages in monkey kidney cell cultures and 7 passages in diploid rhesus cells [55]. Clinical trials for the vaccine in industrialized countries resulted in variable efficacy ranging from 12-90% [20,69,97]. No protection was observed after one dose of RRV-MMU in an impoverished Native American population in the US [85].…”
Section: Rrv-mmumentioning
confidence: 99%
See 1 more Smart Citation
“…59 In 1998, a rhesus-human rotavirus vaccine (RotaShield ® , Wyeth Lederle Vaccines) was licensed in the US after clinical trials in Finland, the US, and Venezuela demonstrated vaccine efficacy of 82-91% against severe rotavirus gastroenteritis. [60][61][62][63] However, the vaccine was withdrawn from the US market less than one year after its licensure due to an association with intussusception at a rate of 1 case per 10,000 vaccinated infants that occurred primarily after the first dose. 33,[64][65][66] Fortunately, despite this setback, vaccine development continued due to recognition of the significant public health burden of rotavirus disease, and both currently licensed vaccines, RV1 and RV5, underwent large prelicensure safety trials with approximately 60,000 to 70,000 infants each.…”
Section: Evolution Of Rotavirus Vaccinesmentioning
confidence: 99%